1993
DOI: 10.1021/ma00056a044
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-crystalline order in mucus

Abstract: Introduction. Mucus plays an exceptionally wide range of important biological roles. It operates as a protective, exchange, and transport medium in the digestive, respiratory, and reproductive systems of humans and other vertebrates (for review see ref 1). It protects fish skin and decreases its hydrodynamic drag,2 and it also functions as a tegumental dehydration barrier, a surface defense, a navigation aid, and a snare for prey in several invertebrate species.3 Its rheological properties are of special inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 1 publication
4
52
0
Order By: Relevance
“…These interactions could stabilize mucin entanglements or even link mucin oligomers alongside most of their contour lengths (i.e., through a zipper-like mechanism). If so, the asymmetry of the mucin macromolecules would lead to the formation of anisotropic networks (27). In addition, Ca 2ϩ could bind other glycoproteins and anionic proteins to the nascent mucin matrix.…”
Section: Gel-forming Mucins: Structural Changes During Biosynthesis Amentioning
confidence: 99%
“…These interactions could stabilize mucin entanglements or even link mucin oligomers alongside most of their contour lengths (i.e., through a zipper-like mechanism). If so, the asymmetry of the mucin macromolecules would lead to the formation of anisotropic networks (27). In addition, Ca 2ϩ could bind other glycoproteins and anionic proteins to the nascent mucin matrix.…”
Section: Gel-forming Mucins: Structural Changes During Biosynthesis Amentioning
confidence: 99%
“…In considering the mucin as a polymer, Verdugo et al (17) have suggested that mucins in the granule matrix must be folded in a non-random conformation. Polarized microscopy images of partially hydrated mucus granules demonstrate that even at visible wavelengths, it is possible to observe the signature of nematic crystalline structures in mucus, which reveals the presence of large-scale supramolecular organization (19).…”
mentioning
confidence: 99%
“…Mucin is known to display liquid crystallinelike behavior, 17 from which it follows that adsorbed thin films are very likely to be birefringent. Hence it seems to be essential to properly consider the anisotropy of self-assembled mucin thin films, unlike the "simple" protein layers that are merely and sufficiently characterized by the number of adsorbed molecules per unit area.…”
mentioning
confidence: 99%